2015
DOI: 10.3109/0886022x.2015.1033368
|View full text |Cite
|
Sign up to set email alerts
|

C4d deposition is associated with immune cells infiltrating in kidney allograft glomerulitis and peritubular capillaritis

Abstract: Objective: The aim of our study was to determine the amount and composition of immune cells within glomeruli and PTCs and its relationship with C4d deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…As shown in Supplementary Table 1, http://links.lww.com/CM9/A726, the glomerulonephritis and peritoneal capillaritis scores of AMR cases were significantly higher than that of all the other diagnoses. It has been reported that the total number of infiltrating cells in glomeruli and PTC are associated with PTC C4d+ and that infiltrating cells in glomeruli and PTC are predominantly macrophages and T cells with a completely cytotoxic phenotype [15] . Both macrophages and cytotoxic T cells can damage endothelial cells and induce lectin-mediated complement pathway activation, [11] which findings support our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Supplementary Table 1, http://links.lww.com/CM9/A726, the glomerulonephritis and peritoneal capillaritis scores of AMR cases were significantly higher than that of all the other diagnoses. It has been reported that the total number of infiltrating cells in glomeruli and PTC are associated with PTC C4d+ and that infiltrating cells in glomeruli and PTC are predominantly macrophages and T cells with a completely cytotoxic phenotype [15] . Both macrophages and cytotoxic T cells can damage endothelial cells and induce lectin-mediated complement pathway activation, [11] which findings support our results.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the total number of infiltrating cells in glomeruli and PTC are associated with PTC C4d+ and that infiltrating cells in glomeruli and PTC are predominantly macrophages and T cells with a completely cytotoxic phenotype. [ 15 ] Both macrophages and cytotoxic T cells can damage endothelial cells and induce lectin-mediated complement pathway activation, [ 11 ] which findings support our results.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, C4d deposits was evident in the region of mononuclear cell accumulations (Figure 5). Deposition of C4d has been recognized to be associated with granzyme B–positive T cells in transplant glomerulitis, 34 adding new dimensions to the regulatory effects of complement on cytotoxic T cell–derived damage. Moreover, allograft recipients who received burixafor treatment had lower plasma levels of CRP relative to the levels of those in the control group (Figure 5C).…”
Section: Discussionmentioning
confidence: 99%